Heliox Improves Carbon Dioxide Removal during Lung Protective Mechanical Ventilation - Charlotte J. Beurskens; Daniel Brevoord; Wim K. Lagrand; Walter M. van den Bergh; Margreeth B. Vroom; Benedikt Preckel; Janneke Horn; Nicole P. Juffermans (Critical Care Research and Practice)
Introduction. Helium is a noble gas with low density and increased carbon dioxide (CO2) diffusion capacity. This allows lower driving pressures in mechanical ventilation and increased CO2 diffusion. We hypothesized that heliox facilitates ventilation in patients during lung-protective mechanical ventilation using low tidal volumes. Methods. This is an observational cohort substudy of a single arm intervention study. Twenty-four ICU patients were included, who were admitted after a cardiac arrest and mechanically ventilated for 3 hours with heliox (50% helium; 50% oxygen). A fixed protective ventilation protocol (6 mL/kg) was used, with prospective observation for changes in lung mechanics and gas exchange. Statistics was by Bonferroni post-hoc correction with statistical significance set at P<0.017. Results. During heliox ventilation, respiratory rate decreased (25±4 versus 23±5 breaths min−1, P=0.010). Minute volume ventilation showed a trend to decrease compared to baseline (11.1±1.9 versus 9.9±2.1 L min−1, P=0.026), while reducing PaCO2 levels (5.0±0.6 versus 4.5±0.6 kPa, P=0.011) and peak pressures (21.1±3.3 versus 19.8±3.2 cm H2O, P=0.024). Conclusions. Heliox improved CO2 elimination while allowing reduced minute volume ventilation in adult patients during protective mechanical ventilation.